PERKEMBANGAN SANITASI DAN PRASARANA KEBERSIHAN DI KOTA BANDUNG AWAL ABAD KE-20 - Budiman, Hary Ganjar (UI Scholars Hub, 2022)
This study aims to show the development of sanitation and hygiene infrastructure in Bandung from the late 19th century to the early 20th century. This research positions sanitation and hygiene infrastructure as part of urban technology that contributes to public welfare. This research used the historical method which consisted of four stages: heuristics, critics, interpretation, and historiography. Results show that sanitation management in Bandung in the early 20th century was conducted by harmonizing technology and natural fortress. Gemeente Bandung anticipated the unhygienic habits of the villagers, environmental pollution, and spread of diseases by providing clean water, toilet facilities, public washing, and an integrated sewage system. The construction of infrastructure that supported sanitation management was carried out from 1910 to 1938. As a result, by 1938, Bandung had already had clean water reservoirs, clean water pipelines, open pipelines for rainwater disposal, closed pipelines for waste disposal, sewage treatment systems, waste treatment management, and road cleaning services.